Developing offender manager competencies in completing case formulation: An evaluation of a training and supervision model. (March 2018) - Radcliffe, Kay; McMullan, Elaine; Ramsden, Jo
The Offender Personality Disorder (OPD) pathway is a national initiative which co-commissions health and probation to work in partnership to enhance the criminal justice management of high risk offenders with personality disorder. Psychologically informed support is expected to augment the current provision for this client group alongside workforce training. The impact of training offender managers (OM) is uncertain and previous research has indicated training may be limited in its effectiveness. This paper examines the impact of a training and supervision model on the quality of formulations produced by offender managers and suggests that a model which teaches formulation through repeated consultation or the live supervision of practice leads to enhanced competencies in completing case formulations. The paper evaluates the quality of formulations produced by offender managers who have had their practice developed through repeated consultation with the OPD pathway (OPDOMs) in comparison with a generic group of offender managers. OPDOMs who have had the longest period of supervision with the project produced the highest quality formulations. The paper acknowledges a number of limitations but suggests that the model under scrutiny may usefully inform service delivery within the Offender Personality Disorder pathway.